Interethnic Interaction Pattern in Karimunjawa Island - Suliyati, Titiek; Rochwulaningsih, Yety; Utama, Mahendra Pudji (Universitas Negeri Semarang, 2017)
This article discusses the interaction patterns in inter-ethnic life that inhabit Karimunjawa which is known to be very heterogeneous. Heterogeneity of Karimunjawa is not only seen in terms of the origin of the migrants, but also language and religion. There are nine ethnics, but three main ethnic inhabit Karimunjawa are Javanese, Madurese and Buginese. Each develops different interaction patterns according to their ethnics. Nonetheless, the social values shared make Karimunjawa communities can live in harmony. They are affected by their perspectives on the sea as a common property right that can be used together regardless of the ethnic background and origin. Therefore, the pattern of harmonious interactions tolerates each other in equal style characterizing the community in Karimunjawa.